OLDER AGE-RELATED ONE-YEAR MORTALITY IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION WITH ST ELEVATION TREATED WITH PERCUTANEOUS CORONARY ANGIOGRAPHY - Milosevic, Aleksandra; Jankovic, Ivana; Glisic, Sofija; Ivanovic, Zarko; Mehmedovic, Amin; Asanin, Milika; Savic-Spasic, Lidija; Matic, Dragan (Medical Research, 2025)
Introduction: The rise in life expectancy has resulted in a greater prevalence of elderly patients presenting with acute myocardial infarction with ST elevation (STEMI).  The Aim: Investigating the association between advanced age and one-year mortality in STEMI patients treated with primary PCI.Material: The study involved 395 STEMI patients who underwent primary PCI and were admitted to the Coronary Care Unit between June and December 2019. The patients were categorised into three age groups: ≤64 years, 65-74 years, and ≥75 years, with the ≤64-year age group as the comparison reference. All-cause mortality was analysed over a one-year period.Results: The mean age of the patients was 62 years; 27.6% were aged between 65 and 74, while 15.7% were 75 years or older. Women accounted for 28.7% of the total, with higher representation in older age groups. Older patients exhibited elevated rates of diabetes, chronic renal insufficiency, anemia, and heart failure (Killip 2-4). Primary PCI rates were notably high across all age groups at 93.3%, 93.6%, and 87.1%, respectively, primarily using a radial approach. The one-year mortality risk was twice as high for those aged 64 to 75 years and seven times higher for those aged 75 and over, with age 75 and above being an independent predictor of all-cause mortality. Conclusion: Elderly patients with STEMI, particularly those aged 75 and older, show a significantly higher one-year mortality rate compared to their younger counterparts aged 64 and younger due to the considerable burden of comorbidities, even when receiving guideline-directed therapies.
Keywords: Elderly, STEMI, primary PCI, mortality